Implementation Strategy Of Good Corporate Governance In Public Companies In Indonesia - Febi Theresia Immanuel; Nurul Laily Oktaviani; Hwihanus Hwihanus (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
It is crucial for public companies in Indonesia to implement Good Corporate Governance (GCG) in order to improve corporate performance, transparency, and accountability. Nevertheless, the implementation of GCG continues to encounter a variety of obstacles and challenges. The objective of this investigation is to evaluate the efficacy of GCG implementation strategies in Indonesian public companies. The qualitative research methodology employed employs data collection methods such as literature studies, surveys, and interviews with practitioners and regulators. At the corporate level, the study's findings indicate that GCG implementation strategies include the establishment of a robust governance structure, the development of suitable policies and procedures, and the enhancement of the responsibilities of the board of commissioners and directors. At the external level, strategies encompass the involvement of stakeholders, the crafting of supportive regulations by regulators and the government, and the provision of education and training to all parties. This study also examines the supporting and inhibiting factors of GCG implementation and offers suggestions to enhance the efficacy of GCG implementation in public companies in Indonesia.